Newly emerged ROS1 rearrangement in a patient with lung adenocarcinoma following resistance to immune checkpoint inhibitors: a case report - Wang, Jian; Liu, Bingyue; Zheng, Qinhong; Xiao, Ruoshui; Chen, Jianxin (Frontiers in Oncology, 2024)
BackgroundROS1, a member of the sevenless subfamily of tyrosine kinase insulin receptors, promotes tumor cell survival, proliferation, and metastasis by activating the JAK/STAT, PI3K/AKT, and MAPK/ERK pathways. It only accounts for about 2% of total NSCLC cases. No cases of acquired ROS-1 rearrangement have been reported worldwide.Case presentationWe reported a case of lung adenocarcinoma without driver alteration that developed resistance to pembrolizumab and newly emerged CD74-ROS1 fusion, and achieved a partial response after entrectinib treatment.ConclusionsWe hypothesize that the newly emerged ROS1 rearrangement occurs as the subset of cells harboring ROS1 gradually becomes the predominant pathological type of adenocarcinoma following pembrolizumab treatment. We propose that new therapeutic targets may emerge for this patient population following long-term immunotherapy. Thus, we advocate for regular monitoring of tumor genetic status, which could yield unexpected benefits.